Strategies for price reduction of HIV medicines under a monopoly situation in Brazil - Gabriela Costa Chaves; Lia Hasenclever; Claudia Garcia Serpa Osorio-; Maria Auxiliadora Oliveira (Universidade de São Paulo, 2015)
ABSTRACT OBJECTIVE To analyze Government strategies for reducing prices of antiretroviral medicines for HIV in Brazil. METHODS Analysis of Ministry of Health purchases of antiretroviral medicines, from 2005 to 2013. Expenditures and costs of the treatment per year were analyzed and compared to international prices of atazanavir. Price reductions were estimated based on the terms of a voluntary license of patent rights and technology transfer in the Partnership for Productive Development Agreement for atazanavir. RESULTS Atazanavir, a patented medicine, represented a significant share of the expenditures on antiretrovirals purchased from the private sector. Prices in Brazil were higher than international references, and no evidence was found of a relationship between purchase volume and price paid by the Ministry of Health. Concerning the latest strategy to reduce prices, involving local production of the 200 mg capsule, the price reduction was greater than the estimated reduction. As for the 300 mg capsule, the amounts paid in the first two years after the Partnership for Productive Development Agreement were close to the estimated values. Prices in nominal values for both dosage forms remained virtually constant between 2011 (the signature of the Partnership for Productive Development Agreement), 2012 and 2013 (after the establishment of the Partnership). CONCLUSIONS Price reduction of medicines is complex in limited-competition environments. The use of a Partnership for Productive Development Agreement as a strategy to increase the capacity of local production and to reduce prices raises issues regarding its effectiveness in reducing prices and to overcome patent barriers. Investments in research and development that can stimulate technological accumulation should be considered by the Government to strengthen its bargaining power to negotiate medicines prices under a monopoly situation.